Diversity of Bivalves of the Mollusca Class in the Bandar Gigieng River, Peukan Tuha Village, Simpang Tiga District, Pidie Regency and Its Use as a Learning Media - Rahmi Agustina; Ervina Dewi; Badratul Nauvis (Jurnal Penelitian Pendidikan IPA, 2022)
The aim of the research was to determine the level of Mollusca Diversity in the Sungai Bandar Gigieng Hamlet, Peukan Tuha Village, Simpang Tiga District, Pidie Regency. This research was carried out using the linetransect and quadratic transect methods. The research location was divided into 3 stations, the stations were divided based on environmental conditions in the river, including the condition of the vegetation and activities occurring in the surroundings, then the samples found were identified. Research results the bivalves found in the Bandar Gigieng Hamlet River, Peukan Tuha Village, Simpang Tiga District, Pidie Regency consist of 2 ordersand 5 species with a total of 102 individuals. The diversity index value of Bivalves in the Bandar Gigieng Hamlet River, Peukan Tuha Village, Simpang Tiga District, Pidie Regency isclassified as medium, with a diversityindexof 1.327555 (H’). Learning activities become more meaningful, students become more active and enthusiastic in directly observing types of aquatic invertebrates